2005
DOI: 10.1111/j.1740-8261.2005.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and Doppler Diagnosis: First Case of Atrial Septal Aneurysm in a Cat

Abstract: A 6-year-old female cat developed pleural and abdominal effusion. Cardiac ultrasound and 2D color tissue Doppler imaging revealed restrictive cardiomyopathy with severe biatrial dilatation and hypertension. This cardiomyopathy was associated with atrial septal aneurysm and a patent foramen ovale. The atrial septal aneurysm involved the entire atrial septum. Necropsy and histological examination confirmed all these findings. ASA is a rare malformation and, as in this cat, it generally occurs concomitantly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…16 Acquired interatrial communications have been associated with important clinical sequelae such as PH, hypoxemia and respiratory distress. 1315,17,18 The patient in this report had HCM and progressive, severe LA enlargement, as well as PH. Dogs with severe LA enlargement and acquired interatrial communication have been reported to develop PH.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…16 Acquired interatrial communications have been associated with important clinical sequelae such as PH, hypoxemia and respiratory distress. 1315,17,18 The patient in this report had HCM and progressive, severe LA enlargement, as well as PH. Dogs with severe LA enlargement and acquired interatrial communication have been reported to develop PH.…”
Section: Discussionmentioning
confidence: 73%
“…Another report describes an atrial septal aneurysm with bidirectional shunting in a cat with severe right atrial enlargement and restrictive cardiomyopathy. 15 The authors of that report described an atrial septal aneurysm where the entire IAS was abnormal, likely indicating underlying congenital pathology of the IAS. 15 The cat described in this report was born with a structurally normal IAS with a valve-competent PFO; however, interatrial shunting was not present prior to severe LA enlargement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Doğumdan sonra değişen sürelerde, sol atriumdaki basıncın artması sonucunda, valvula foraminis ovalis adı verilen kapak benzeri bir membran tarafından delik kapatılır (6). Bu süreç sığırlarda doğumdan sonraki birkaç ay içerisinde tamamlanmaktadır (11).…”
unclassified
“…Yetişkin insanlarda % 25-30 oranında görülen bu durum (3), sığırda (12), atta (9), köpekde (4), kedide (6) ve domuzda (5) tanımlanmıştır. Çoğunlukla klinik semptom göstermeyen kalıcı foramen ovale olguları, kalp oskültasyonunda karakteristik üfürüm seslerinin duyulması ve kontrast ekokardiyografide defektin görüntülenmesi ile teşhis edilebilmektedir (6,12). Sağdan sola şant sonucunda gelişen kalp hipertrofisi, emboli oluşumu ve felç nadiren gözlenen klinik bulgulardır (6,10).…”
unclassified